(untitled) (Third Sector Social Economic Review, 2015)
Social exclusion signifies the process through which the individual is deprived totally or partially of the social, economic, political and cultural systems that ensures his or her social accommodation. In terms of women, the main actor of this study, the phenomenon of social exclusion may be defined as “the situation of being out of the social, economic, political and cultural institutions and systems, which leads to ignore his or her very existence and prevents his or her integration to society”. Especially poor women always feel and experience social exclusion process more intensely than men do. The main argument of this study is that the poverty of women, which constitues an obstacle for them to enter into public space, becomes more effective when combined with social exclusion, and causes more exclusion for women than men. The argument that ‘among poor women, those who are divorced, abandoned, and still sexually attractive young ones are more excluded than the others’ is also analyzed.